Successful treatment of peritonitis caused by Acremonium species without catheter removal: Case report and literature review - Zhuang, Zhen; Li, Yuehong; Wu, Xianglan; Wang, Wei; Cao, Mingxia; Xiao, Nan (The Journal of Infection in Developing Countries, 2023)
Introduction: It is a rare case of continuous ambulatory peritoneal dialysis-related peritonitis associated with Acremonium sp. infection. Case presentation: Symptoms of Acremonium infection peritonitis are hidden and atypical, leucocytes in ascites are moderately elevated, and general bacterial culture difficulty obtains positive results. In this report, a patient with peritoneal dialysis-related peritonitis caused by Acremonium species was successfully treated without catheter removal in our hospital. The organism species was cultured from a catheter and PD effluent fluid. The patient’s peritonitis did not relapse within 6 months. Conclusions: Once a patient on peritoneal dialysis was infected with fungal peritonitis, the outcome was usually to remove the tube and stop peritoneal dialysis. In this case, our experience is that using a catheter-salvage therapy method, we can successfully cure PD-related peritonitis associated with Acremonium sp.